2021
DOI: 10.3390/ijms22031179
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Delivery and Gene Therapy in Pulmonary Hypertension

Abstract: Pulmonary hypertension (PH) is a progressive complex fatal disease of multiple etiologies. Hyperproliferation and resistance to apoptosis of vascular cells of intimal, medial, and adventitial layers of pulmonary vessels trigger excessive pulmonary vascular remodeling and vasoconstriction in the course of pulmonary arterial hypertension (PAH), a subgroup of PH. Multiple gene mutation/s or dysregulated gene expression contribute to the pathogenesis of PAH by endorsing the proliferation and promoting the resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 328 publications
(214 reference statements)
0
14
0
Order By: Relevance
“…In the past years, several groups have explored gene therapy as a strategy to improve or correct PAH in different models. Targets of interest that have been studied include several of genes and viral vectors [35]. It should be noted that in recent years that AAV vector has gained popularity in translational medicine [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, several groups have explored gene therapy as a strategy to improve or correct PAH in different models. Targets of interest that have been studied include several of genes and viral vectors [35]. It should be noted that in recent years that AAV vector has gained popularity in translational medicine [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapies targeting the pulmonary endothelium have been identified for the treatment of genetic disorders such as alpha-1 antitrypsin deficiency (AATD) and pulmonary arterial hypertension (PAH). , AATD is caused by a mutation in the AAT gene that encodes a protease inhibitor that protects against inflammatory damage. While endogenous AAT is produced in the liver, transduction of pulmonary ECs with the AAT gene may offer a more direct treatment for AATD-associated illnesses that affect the lung such as emphysema. , PAH can be caused by a number of factors including loss-of-function mutations in caveolin-1 (CAV1), which acts as a scaffolding protein in caveolae membranes and regulates signaling complexes relevant to PAH including eNOS activity.…”
Section: Nucleic Acid Therapies For Endothelial Pathologiesmentioning
confidence: 99%
“…Recent studies have found that Apela, also known as ELABELA/Toddler/ELA32, a new ligand of the apelin peptide jejunum (APJ) receptor, not only plays an important biological role in heart development, heart failure, and maintaining fluid balance and angiogenesis but also has an important biological effect in reducing pulmonary hypertension and improving right heart function exhaustion in a pulmonary artery rat model 5–10 . Previous studies have shown successful effects of gene therapy in pulmonary hypertension 11 . This study further explores the biological effect and potential molecular mechanism of adeno‐associated virus (AAV)‐mediated Apela gene therapy in a rat model of pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%